2020
DOI: 10.1002/gj.3912
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐proxy based high‐resolution stratigraphical analysis of the possible Palaeocene–Eocene boundary interval, Salt Range, Pakistan

Abstract: The Palaeocene–Eocene boundary (PEB) interval has been recognized in the Patala Formation, Nammal Gorge Section, Pakistan using lithostratigraphy, stable carbon isotope stratigraphy and integrated biostratigraphy. Four distinct lithological units are identified in the Patala Formation in stratigraphic order from bottom to top; unit‐1 to unit‐4. The top of unit‐3 hosts three closely spaced unconformities demarcated as U1, U2, and U3. The PEB interval is represented by a negative shift of 1.61‰ in δ13CV‐PDB repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In this basin, the onset of the carbon and oxygen stable isotope excursion has proved that it's associated with the PETM (Hanif, 2011). Besides isotopic evidences, paleontological ones also support that the PTEM impacted the area neighboring the Salt Range (Afzal et al, 2011;Hanif et al, 2020) and indicate that the environment fluctuated (bathyal -shallow carbonate platform; Hanif et al, 2020). Still, to our knowledge, the studies about the PTEM effects in this region are still scarce, therefore arising the need for further investigations based on petrographic (e.g.…”
Section: Origin Of the Eocene Halite In The Kohat Basinmentioning
confidence: 64%
“…In this basin, the onset of the carbon and oxygen stable isotope excursion has proved that it's associated with the PETM (Hanif, 2011). Besides isotopic evidences, paleontological ones also support that the PTEM impacted the area neighboring the Salt Range (Afzal et al, 2011;Hanif et al, 2020) and indicate that the environment fluctuated (bathyal -shallow carbonate platform; Hanif et al, 2020). Still, to our knowledge, the studies about the PTEM effects in this region are still scarce, therefore arising the need for further investigations based on petrographic (e.g.…”
Section: Origin Of the Eocene Halite In The Kohat Basinmentioning
confidence: 64%
“…Hanif et al (2014) focused on dinocysts (Axiodinium; Williams et al, 2015;Fensome et al, 2009, previously as Apectodinum) abundance and its correlation to the Palaeocene-Eocene boundary with the help of carbon isotopic excursion (CIE). Whereas the latest findings of Hanif et al (2020) did place the possible P-E boundary based on CIE and RD-assemblages but the interval contains the signature of dissolution caused by the ecological artefact. This dissolution affected the quality so that the boundary remained less precisely marked.…”
Section: Introductionmentioning
confidence: 90%
“…However, the exact location of the PETM has not precisely been located yet. Recently, Hanif et al (2020) have reported detailed stratigraphical analysis of the P-E boundary interval from the Salt Range, Upper Indus Basin. They used a multi-proxy approach such as lithostratigraphy, stable isotopes, foraminifera, organic dinoflagellates, as well as calcareous nanno-plankton, for better understanding the P-E interval, according to the latest available literature, references therein in Hanif et al (2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger benthic foraminifera (LBF) are a useful tool for biostratigraphical and palaeoenvironmental interpretations (Gary, 1991;Hallock & Glenn, 1986;Hanif et al, 2021;Papazzoni et al, 2017;Serra-Kiel et al, 1998;Zoeram et al, 2015). The LBF are significant contributors to shallow marine sediments in the tropical and subtropical regions during the Early Palaeogene, and occasionally they formed prolific accumulations along the western, central, and eastern regions of Neo-Tethys (e.g., Drobne, 1977;Hӧttinger, 1960;Özcan, 2002;Racey, 2001;Schaub, 1981).…”
Section: Introductionmentioning
confidence: 99%